Flow effect on lesion formation in RF cardiac catheter ablation - Cao, Hong; Vorperian, Vicken R.; Tungjitkusolmun, Supan; Tsai, Jang Zern; Haemmerich, Dieter; Choy, Young Bin; Webster, John G. (My University, 2001)
This study investigated the flow effect on the lesion formation during radio-frequency cardiac catheter ablation in temperature-controlled mode. The blood flow in heart chambers carries heat away from the endocardium by convection. This cooling effect requires more power from the ablation generator and causes a larger lesion. We set up a flow system to simulate the flow inside the heart chamber. We performed in vitro ablation on bovine myocardium with three different flow rates (0 L/min, 1 L/rain and 3 L/min) and two target temperatures (60 °C and 80 °C). During ablation, we also recorded the temperatures inside the myocardium with a three-thermocouple temperature probe. The results show that lesion dimensions (maximum depth, maximum width and lesion volume) are larger in high flow rates (p < 0.01). Also, the temperature recordings show that the tissue temperature rises faster and reaches a higher temperature under higher flow rate.
Keywords: Ablation; Cardiac catheter ablation; Convection film coefficient; Lesion dimension; RF cardiac catheter ablation; Temperature recording